FOOD SAFETY CONCERNS INFLUENCE NEOPHOBIC RESPONSE TOWARDS KADAZANDUSUN TRADITIONAL FOOD IN DOMESTIC TOURISTS - Dg Khairunisa Binti Ahmad Sapawi; Yasmin Beng Houi Ooi; Shalawati Binti Ibrahim; Lai Yee Czhing (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Gastrotourism is a major component of a country’s tourism activity and traditional food is one of its core products. However, food safety concerns and food neophobia in tourists have become an obstacle in effectively promoting local traditional foods. The objective of this study was to measure food neophobia and food safety concerns in domestic tourists toward Kadazandusun traditional food. A total of 600 domestic tourists from Peninsular Malaysia were recruited from places frequented by tourists and shopping malls in Kota Kinabalu city. They completed self-administered questionnaires on food neophobia and food safety concerns. Most respondents were ranged from not neophobic to having slight food neophobia. In food neophobia, doubts about cleanliness, perception of weirdness of traditional foods, and unpleasant display were the main reasons. The tourists’ religious background, educational levels, annual income and region of origin were also factoring that influenced their acceptance of these traditional foods. In conclusion, to help tourists appreciate Kadazandusun traditional foods, there are rooms for improvements in their presentation, incorporation of fusion cooking, and increasing promotion efforts through mass media.